An Analysis of Textbook “ When English Rings a Bell” for Junior High School Grade Eight - Abdul Syahid; Rahmania Ananda; Amanda Salsabila; Sumarni, Sumarni; Florence Angelaila Fauzi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Textbooks are an important learning tool in the education system. It becomes more important when English is learned as a foreign language like in Indonesia. As a language learned other than the mother tongue, most likely English is only learned by Indonesian students in the classroom. As a result, English textbooks have the potential to be students' only access to language in the classroom. The purpose of this study was to find out whether the book "When English Rings a Bell" for the eighth grade of junior high school is by the criteria (Education National Standard Council) BSNP. In this study, researchers used methods of content analysis, presentation analysis, language analysis, and graphic analysis based on BSNP (National Education Standards Board) which focuses on language characteristics as communication by paying attention to text content. This research instrument is a document. Researchers will focus 13 chapters on grade VIII junior high school. Then a check is carried out using the suitability check of textbooks based on BSNP (Education National Standard Council). The result of this study, the quality of the "When English Rings a Bell" textbook for the eighth grade of Junior High School based on the Education National Standard Council (BSNP) is good. There are 4 elements, these are content eligibility, presentation eligibility, language eligibility, and graphic eligibility. But, for the content eligibility element side, not all items of its indicators are fulfilled clearly. Just for KD and KI there are not found in this textbook.